2000
DOI: 10.1007/s004200000117
|View full text |Cite
|
Sign up to set email alerts
|

8-Hydroxydeoxyguanosine in leukocyte DNA and urine of quartz-exposed workers and patients with silicosis

Abstract: Our findings suggest that a less effective repair of 8-OHdG is associated with a higher degree of pulmonary airway obstruction in patients with silicosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…The lack of correlation between the 8-oxodG concentrations in lymphocytes and urine is in agreement with other studies (26). Correlations may not be expected as 8-oxodG concentration in nuclear cell DNA reflects the balance between formation and repair, whereas the urinary excretion supposedly reflects the summed rates of formation and turnover of 8-oxodG in nuclear and mitochondrial DNA as well as the nucleotide pool in the whole body (14).…”
Section: Discussionsupporting
confidence: 90%
“…The lack of correlation between the 8-oxodG concentrations in lymphocytes and urine is in agreement with other studies (26). Correlations may not be expected as 8-oxodG concentration in nuclear cell DNA reflects the balance between formation and repair, whereas the urinary excretion supposedly reflects the summed rates of formation and turnover of 8-oxodG in nuclear and mitochondrial DNA as well as the nucleotide pool in the whole body (14).…”
Section: Discussionsupporting
confidence: 90%
“…Overall, this has led to urinary measurements of thymine glycol being superseded by those of 8-oxodG and the subsequent widespread use of HPLC ECD. A number of methods based on column-switching HPLC with regular reverse phase (usually C18) separative columns and ECD for assay of 8-oxodG have been developed (24)(25)(26)(27)(28). The pre-purification, or extraction, columns have differed in their packing material, using generally C18 or ion exchange separation approaches.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…In this study no association between 8-OHdG and the individual cumulative dust exposure was found, nor was there a synergistic eVect between smoking and occupational exposure. Pilger et al (2000) determined urinary 8-OHdG and 8-OHdG in leukocyte DNA of 63 workers occupationally exposed to quartz and 42 patients with silicosis. No signiWcant diVerences in 8-OHdG between healthy workers and silicosis patients were observed.…”
Section: Silicamentioning
confidence: 99%